2016
DOI: 10.1080/08870446.2016.1193178
|View full text |Cite
|
Sign up to set email alerts
|

Brain drawings following traumatic brain injury (TBI) and links to illness perceptions and health outcomes – Findings from a population-based study

Abstract: Drawings post-TBI offer a simple, cost- and time-effective way to begin discussions and improve understanding of peoples' illness perceptions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(20 citation statements)
references
References 59 publications
0
20
0
Order By: Relevance
“…The number of participants in those studies ranged from 30 to 245. Four of the studies were conducted in New Zealand (Jones et al, 2016;Jones et al, 2019;Snell et al, 2013;Snell et al, 2011), two in Australia (Anderson & Fitzgerald, 2018;Sullivan et al, 2014), two in India (Var & Rajeswaran, 2012;War & Rajeswaren, 2013), one in the USA (Bahraini et al, 2018), and one in the UK (Whittaker et al, 2007). Five of the studies collected their data using prospective longitudinal observations (Anderson & Fitzgerald, 2018;Jones et al, 2016;Snell et al, 2013;Snell et al, 2011;Whittaker et al, 2007), four used a cross-sectional design (Bahraini et al, 2018;Sullivan et al, 2014;Var & Rajeswaran, 2012;War & Rajeswaren, 2013), and one used a retrospective design (Jones et al, 2019).…”
Section: Characteristics Of Included Studiesmentioning
confidence: 99%
“…The number of participants in those studies ranged from 30 to 245. Four of the studies were conducted in New Zealand (Jones et al, 2016;Jones et al, 2019;Snell et al, 2013;Snell et al, 2011), two in Australia (Anderson & Fitzgerald, 2018;Sullivan et al, 2014), two in India (Var & Rajeswaran, 2012;War & Rajeswaren, 2013), one in the USA (Bahraini et al, 2018), and one in the UK (Whittaker et al, 2007). Five of the studies collected their data using prospective longitudinal observations (Anderson & Fitzgerald, 2018;Jones et al, 2016;Snell et al, 2013;Snell et al, 2011;Whittaker et al, 2007), four used a cross-sectional design (Bahraini et al, 2018;Sullivan et al, 2014;Var & Rajeswaran, 2012;War & Rajeswaren, 2013), and one used a retrospective design (Jones et al, 2019).…”
Section: Characteristics Of Included Studiesmentioning
confidence: 99%
“…In many contexts, scientists have tried to quantify the subjective expression of a drawn person, an assignment used in clinical practice to deepen experience through verbal exchange with a therapist (Penzes et al, 2018). Assessment of illness experience through drawings has been examined, for instance, in people with cardiovascular disease (Broadbent et al, 2006;Reynolds et al, 2007), brain injury (Jones et al, 2016), eating disorders (Guez et al, 2010), Cushing's syndrome (Tiemensma et al, 2012), and chronic pain disorders including headache (Broadbent et al, 2009), whiplash-associated disorders (Bernhoff et al, 2017), and fibromyalgia (Bojner Horwitz et al, 2006). These studies in patients with somatic problems indicated that drawings reveal clinical severity, illness perception and distress (Broadbent et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…However, when body-and illness-related issues need to be assessed, drawings have been found to be of value. Research in patients with cardiovascular diseases (Broadbent, Ellis, Gamble, & Petrie, 2006;Reynolds, Broadbent, Ellis, Gamble, & Petrie, 2007), headache (Broadbent, Niederhoffer, Haguec, Corter, & Reynolds, 2009), brain injury (Jones et al, 2016), eating disorders (Guez, Lev-Wiesel, Valetsky, Kruszewski Sztul, & Pener, 2010) and Cushing's syndrome (Tiemensma et al, 2012) showed correlations between objective physical features of drawings of the affected body part, such as size or detail, and clinical severity, illness perception and distress. Moreover body drawings have been indicated to be sensitive to change in a small randomised controlled trial involving dance movement therapy for patients with fibromyalgia; the intervention group used more details and made larger drawings of themselves after six months of therapy than the treatment-as-usual group (Bojner Horwitz, Kowalski, Theorell & Anderberg, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Our study was primarily designed to test the premise that certain characteristics of body drawings can give an indication of the severity of the troubled relationship to the client's body. In analogy to most illness-related research of drawings (e.g., Guez et al, 2010;Jones et al, 2016;Tiemensma et al, 2012), we chose to evaluate a rating procedure focusing on objective characteristics of body drawings as these can be scored in a quantitative, scientifically reliable way (Chirila & Feldman, 2012) and such a procedure is more easily applied and replicated by others. Therefore, the aim of our study was to examine whether objective features of own body drawings, made by people with somatoform disorder, can produce complementary information to self-report questionnaires of own body experience.…”
Section: Introductionmentioning
confidence: 99%